2021
DOI: 10.1002/anbr.202100026
|View full text |Cite
|
Sign up to set email alerts
|

Recent Strategies for Strengthening and Stiffening Tough Hydrogels

Abstract: Hydrogels are major components of the human body. To replace a damaged hydrogel in the body or support/monitor its normal operation, artificial hydrogels similar to those found in nature are required. As the development of morphologically adaptable soft yet tough hydrogels such as double‐network (DN) and polyampholyte (PA) gels, they are applied to soft tissues such as the neural and epithelial tissues with elastic moduli ranging from a few pascals to several kilopascals. However, creating strong and stiff hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 171 publications
(275 reference statements)
0
28
0
Order By: Relevance
“…When a load is applied to these materials, it will be transferred from the polymer to the stiffer filler (in our case, the cross-linked Gel MS and the mineral-containing MS), which will bear part of the load, increasing the global mechanical properties. 45 We observed that the extent of these changes highly depended on the nature of each MS. Precisely, Gel MS doubled the G′ eq compared to the control, Gel-HA MS presented a > 10-fold increase, while for CDHA MS only a limited gain was observed.…”
Section: Discussionmentioning
confidence: 77%
“…When a load is applied to these materials, it will be transferred from the polymer to the stiffer filler (in our case, the cross-linked Gel MS and the mineral-containing MS), which will bear part of the load, increasing the global mechanical properties. 45 We observed that the extent of these changes highly depended on the nature of each MS. Precisely, Gel MS doubled the G′ eq compared to the control, Gel-HA MS presented a > 10-fold increase, while for CDHA MS only a limited gain was observed.…”
Section: Discussionmentioning
confidence: 77%
“…Thermosensitive polymers (such as PNIPAAm, Soluplus) can be incorporated into the backbone to fabricate highly biocompatible thermoresponsive hydrogels for bone defects requiring minimally invasive surgery ( Xue et al, 2021 ). However, such hydrogels usually have poor mechanical properties and need to be composited with other materials to enhance the strength of the matrix ( Ahmed, 2015 ; Bahram et al, 2016 ; Fuchs et al, 2020 ; Ji and Kim, 2021 ). It has been found that incorporating of HA into thermally responsive hydrogel systems can enhance the physical mechanics performance of the hydrogels.…”
Section: Hydrogels In Bone Diseasesmentioning
confidence: 99%
“…This behavior of zwitterionic hydrogels is known as the anti-polyelectrolyte effect. From the application point of view, this poses serious problems: (1) as biomedical engineering materials, the mechanical properties of zwitterionic hydrogels can only match part of the soft tissues but are far from the requirements of stiff load-bearing tissues (fracture strength 1–200 MPa, elastic modulus 0.01–3 GPa) [ 32 ]; (2) as a quasi-solid electrolyte, zwitterionic hydrogels have to face a trade-off between swelling in ionic solutions and loss of mechanical properties [ 33 ].…”
Section: Characteristics Of Zwitterionic Hydrogelsmentioning
confidence: 99%